PENGARUH NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO DAN BOPO TERHADAP ROA PADA SEKTOR PERBANKAN YANG TERDAFTAR DI OJK PERIODE 2017-2021 - Sulistiana, Ni Kadek Devi; Geriadi, Made Ayu Desy (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2024)
The purpose of this research is to identify the impact of non-performing loans (NPL), loan to deposit ratio (LDR), and operational income operating costs (BOPO) on return on assets (ROA) in corporate banking. This research was conducted on banking sector corporations registered with the Financial Services Authority (OJK) in the 2017-2021 period. Purposive sampling was used as a sampling method involving 64 sample issuers. Quantitative data and secondary data used in research. Observation and documentation studies are used as collection techniques. Multiple linear regression analysis was used as a data analysis technique. The research results indicate that simultaneously, return on assets (ROA) is significantly influenced by non-performing loans (NPL), loan to deposit ratio (LDR) and operational income operating costs (BOPO). Partially, return on assets (ROA) is significantly negatively affected by non-performing loans (NPL) and operating income operating costs (BOPO), on the other hand, return on assets (ROA) is significantly influenced positively by the loan to deposit ratio (LDR).